LANDSCAPE SENSITIVITY: FROM THEORY TO PRACTICE - Usher M.B. (My University, 2001)
Landscape sensitivity is expressed as the ratio of the change in a system to the change in a landscape component. The larger the ratio, the greater the sensitivity. An array of drivers of landscape change is reviewed, but there is seen to be little benefit in separating natural changes from human-induced changes: most change has a component of each, though there is a continuum from one extreme to the other.Changes in the systems themselves are reviewed, including the increasing evidence for two or more system states being possible. Whilst one state may be preferred, there is no consensus on what kind of a landscape we want, or how aspects of that landscape can be manipulated to give us what we want. This is a field of research were really new ideas are wanted, and where interdisciplinary research should be the norm.
Keywords: COUNTRYSIDE MANAGEMENT; LANDSCAPE CHANGE; LANDSCAPE SENSITIVITY; LAND-USE CHANGE; NATURAL SYSTEMS